Micro-scale corrosion behaviours of the Fe-based amorphous alloy coating in alkaline solutions in three-dimensions - Yiliyaer Hairule; Dandan Liang; Tiantian Chen; Yongming Zhang; Xianshun Wei; Qing Chen; Wen Li; Bo Chen (Journal of Materials Research and Technology)
Despite extensive research on the corrosion of the Fe-based amorphous alloy coatings (AACs) has been carried out, yet, regarding the corrosion morphology of the Fe-based AACs in NaOH solution, the current findings only indicate the existence of localized corrosion, without clarifying the occurrence and mechanism of pitting corrosion. This work investigated the corrosion behaviours of the Fe-based AACs in NaOH solutions through three-dimensional (3D) structure and morphology analysis cooperating with electrochemical testing. The work widens the pitting corrosion mechanism of the AACs. The results show that the Fe-based AACs in NaOH solution have an obvious secondary passivation phenomenon, and serious pitting corrosion occurs. As the concentrations of the NaOH solutions increase, the corrosion resistance of AACs gradually decreases. Additionally, the corrosion rates of the AACs are calculated directly based on the (pore) volume changes before and after corrosion treatments through X-ray micro-computed tomography (X-ray micro-CT) measurements, which provides a new method for the corrosion rate calculation.